Information activity of an individual as a condition of information openness of society - Dobrorodnii, Danila G. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
Openness is one of the main characteristics of the information society, and it is interpreted as free access to information. Openness is perceived as a fundamental value and characteristic of society, the most important personality trait, development goal, and also a mean of realizing specific tasks. However, social and individual strategy of informational openness in a global information space is a high-risk strategy, involving high uncertainty of the results and the likelihood of negative consequences, for example, the emergence of digital inequality. The condition for constructive implementation of the principle of information openness is information activity, which is understood as the ability and readiness of an individual to independently obtain reliable and useful information.